Parallel Regulation of Charge Dynamics on Bipolar Ferroelectric Surfaces Breaks the Limits for Water Splitting Efficiency - Zhang, Jie (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 Wiley‐VCH GmbH.